2023
DOI: 10.1021/acscatal.3c03487
|View full text |Cite
|
Sign up to set email alerts
|

7-Azaindole N-Oxide (7-AINO) Mediated Cu-Catalyzed N-Arylation: Mechanistic Investigation into the Role of Fluoride Ions

Krishanu Mondal,
Narottam Mukhopadhyay,
Susanta Patra
et al.

Abstract: A Cu­(II) fluoride-catalyzed N-arylation of 7-azaindole N-oxides (7-AINO) has been developed using boronic acid under base-free conditions. During the process, a combination of spectroscopy and crystallography techniques has identified the exact formulation of key reaction intermediates that allowed to propose a complete mechanistic description establishing the role of 7-AINO as a ligand and deducing the crucial role of fluoride ions (F–) in the entire catalytic cycle. A monomeric Cu­(II)-7-AINO complex (4) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…Das and co-workers found that these dimeric species tend to be solvent dependent, and tended to observe a discrete CuL 2 complex crystallised from methanol (using copper( ii ) fluoride) and selective crystallisation of the axially-coordinated dimer 1 only when recrystallised from dichloromethane/hexane. 13 In our hands, using copper acetate as the copper source we observed only the axially bridged dimer and minute quantities of the methoxide bridged species.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…Das and co-workers found that these dimeric species tend to be solvent dependent, and tended to observe a discrete CuL 2 complex crystallised from methanol (using copper( ii ) fluoride) and selective crystallisation of the axially-coordinated dimer 1 only when recrystallised from dichloromethane/hexane. 13 In our hands, using copper acetate as the copper source we observed only the axially bridged dimer and minute quantities of the methoxide bridged species.…”
Section: Resultsmentioning
confidence: 58%
“…16 Recently, Das and co-workers reported the room-temperature structure of a triclinic hydrate of HL crystallised from dichloromethane/hexane, which exhibited similar angled hydrogen-bonded dimers between HL units. 13 Despite the less hydrophilic crystallisation solvent, association of water was still observed in that case, giving a hemihydrate HL ·0.5H 2 O.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several coordinating ligands, such as N,N'-dimethylethylenediamine (DMEDA)and N,N,N',N'-tetramethylethylenediamine (TMEDA), [33] pyridine N-oxide, [34] thiophene-2carboxylate (TC), [35] 1,10-phenanthroline (phen) [36] and 4-(Dimethylamino)pyridine (DMAP), [37][38][39] have been found promoting various copper catalysed CÀ N bond forming [40][41][42] reactions. These ligands help in preventing copper aggregation, enhancing solubility, stimulate milder conditions and stabilise active catalyst species during the catalysis process.…”
Section: Introductionmentioning
confidence: 99%